Implementation Of Multicultural-Based Character Values To Remind Tolerance For Diversity In Social Studies Learning (Exploratory Study on MTs Students) - Iswan Riyadi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Multicultural Education plays a major role in Indonesian educational institutions. Our cultural, racial, religious, socioeconomic, and other distinctions are seen as particularly strong selling points for the United States. Although God has blessed us with a wide variety of people and cultures, this diversity frequently leads to friction between different social groupings and even individuals. Integrating ethical and spiritual principles into the classroom is what's known as